2022
DOI: 10.1002/dac.5191
|View full text |Cite
|
Sign up to set email alerts
|

Design of wideband planar antenna with inverted I‐shaped tuning stubs for application in 5G, satellite communication, and Internet of Things

Abstract: In this article, a wideband planar antenna is proposed for 5G mobile communications, satellite communication, and Internet of Things (IoT)-enabled applications. The proposed antenna consists of a rectangular radiating patch and two I-shaped tuning stubs, excited by two I-shape microstrip lines. The antenna of size (17 Â 20 Â 1) mm 3 is designed using FR4 material having a dielectric constant (ε r ) of 4.4. Simulated results illustrate that the antenna operates with a radiation efficiency of 90% and a peak gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Researchers have demonstrated remarkable achievements in achieving multiband behavior by adopting various novel techniques and materials. For instance, metamaterial-inspired structures [3][4][5][6], frequency selective surfaces (FSS) [7][8][9], and advanced tuning methods have been employed to broaden the operating bandwidth and enhance the performance of these antennas [10][11][12][13]. Moreover, studies have shown that multiband patch antennas can significantly enhance the spectral efficiency and overall capacity of 5G networks [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated remarkable achievements in achieving multiband behavior by adopting various novel techniques and materials. For instance, metamaterial-inspired structures [3][4][5][6], frequency selective surfaces (FSS) [7][8][9], and advanced tuning methods have been employed to broaden the operating bandwidth and enhance the performance of these antennas [10][11][12][13]. Moreover, studies have shown that multiband patch antennas can significantly enhance the spectral efficiency and overall capacity of 5G networks [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%